Ecotourism Development Strategy in Dago Mountain Tourist Attraction - Dustin (Journal of Humanities and Social Sciences (JHASS), 2023)
Mount Dago is located in Dago village, Cikuda Wanaherang, Parung Panjang, Bogor city, West Java. This tourist spot is arguably still quite new in the city of Bogor, because it was only inaugurated around 2019 yesterday. the natural tourist area of Mount Dago is on land owned by Perhutani. Then handed over to residents to be managed through the Village and Forest Community Organization (LMDH) as a tourist area. The area is also about 10 hectares. The ecosystem in this area is also well maintained by the management of the tourist area.This study aims to determine the Ecotourism Development Strategy at Mount Dago Tourism. The method used in the research is qualitative using triangulation data validity.